Benedetta and the creation of ‘Second Futurism’ - Larkin, Erin (Journal of Modern Italian Studies, 2013)
Despite the recent vogue in studies on Futurism, writer and artist Benedetta Cappa Marinetti has received little critical attention. Few scholarly works have focused on her essays regarding woman and the Fascist state, and in particular the role of mother. It has been argued that these texts support not only the position that women futurists - in adhering to a movement remembered for its disprezzo della donna - were victims of their self-accepting inferiority, but also the view that Futurist attitudes towardswomen were a precursor of Fascist-era gender politics. Larkin challenges this position, and discusses crucial new archival research, which reveals how maternity in Benedetta's works is actually linked to her radical new reformulation of Futurism. Far from seconding woman's inferior position within the avant-garde, or indeed the Fascist state, Benedetta uses the issue of maternity subtly to subvert her status - in both the movement and society - from within. © 2013 Taylor & Francis.
Keywords: Avant-garde; Benedetta; Cappa; Futurism; Marinetti; Women writers; dept.wll

La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 - Larkin, Erin (2026)
La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 is an open-access digital humanities project documenting the professional and civic life of New Haven's Italian American community between 1890 and 1930. The archive is based on Antonio Cannelli's La Colonia Italiana di New Haven (1921), a 373-page Italian-language volume combining a community Who's Who with a survival guide for new immigrants. Cannelli documented 248 individuals and more than 90 businesses, including physicians, attorneys, pharmacists, musicians, grocers, and bankers. Cannelli published his volume in 1921, the same year that Nicola Sacco and Bartolomeo Vanzetti went on trial for murder in Massachusetts; they were convicted on July 14, 1921, and sentenced to death in a case that became an international cause célèbre and a defining watershed of anti-immigrant sentiment directed specifically at Italians. The trial unfolded against a broader landscape of systematic exclusion: the Emergency Quota Act of 1921 had passed just months earlier, sharply restricting Southern and Eastern European immigration, and Italians faced sustained targeting, marginalization, and persistent characterization as unskilled, unassimilable, and threatening. Cannelli's documentation was deliberate advocacy in precisely this climate: a counter-narrative assembled to demonstrate the professional achievement, civic engagement, and cultural diversity and richness of a community that dominant American discourse refused to acknowledge. La Colonia Digital Archive makes that narrative searchable and accessible to researchers, descendants, and the general public, plotting archival documents and photographs onto contemporary maps of New Haven and the surrounding area. The archive is currently in active pre-launch development. Public release is planned for 2026, with ArcGIS StoryMap components to be added through 2026–2027.
Keywords: Cultural heritage; Digital Archives; Diversity (politics); Documentation; Haven; Narrative; dept.wll

Futurist arte / vita: Benedetta Fictionalized - Larkin, Erin (Volume 8 2018, 2018)
Keywords: dept.wll